Ivermectin as a promising therapeutic option for onchocerciasis‐associated epilepsy - Mohammad Amin Manavi; Razieh Mohammad Jafari; Hamed Shafaroodi; Mohammad Sharifzadeh; Ahmad Reza Dehpour (Epilepsia Open)
Abstract Onchocerciasis, commonly known as river blindness, is a neglected tropical disease caused by the parasite Onchocerca volvulus. It can lead to blindness and visual impairment. Studies have also demonstrated a link between onchocerciasis and epilepsy, with there being a correlation between onchocerciasis endemicity and epilepsy prevalence. Onchocerciasis‐associated epilepsy (OAE) emerges predominantly in individuals aged 3–18, with a notable prevalence in regions where onchocerciasis transmission persists. These areas exhibit elevated rates of epilepsy, underscoring the significant impact of ongoing onchocerciasis on the incidence of epilepsy, particularly within the specified age range. Both epilepsy prevalence and incidence have evolved over the past three decades in a Tanzanian area endemic for onchocerciasis. Researchers have studied the effects of the antiparasitic drug ivermectin on OAE. About one third of Ugandan patients saw reduced seizure frequency or intensity after one 150 μg/kg dose. Clinical research in the Congo among infected epileptics on anti‐seizure medications (ASMs) suggested ivermectin may decrease seizure frequency following oral administration of ivermectin tablets (3 mg). Beyond its antiparasitic properties, ivermectin has demonstrated anticonvulsant effects against clonic and tonic–clonic seizures, likely through modulation of GABAA receptor and neuroinflammation. There is evidence of synergistic effects when combined with GABAergic ASMs like diazepam. As neuroinflammation plays a key role in OAE, ivermectin's anti‐inflammatory properties by inhibiting cytokines like TNF‐α and IL‐1β are also relevant. While certain other antiparasitic drugs can interact with ASMs and have side effects like seizures, no such interactions or side effects have been reported for ivermectin. However, there is a need for more randomized controlled trials specifically evaluating ivermectin's impact on seizures in O. volvulus‐infected epileptics on ASMs. Given its efficacy against parasites, limited side effects, and potential anticonvulsant mechanisms, ivermectin could be a favorable first‐line treatment option, but further research is warranted to confirm benefits for OAE. Plain Language Summary This article explores the potential benefits of ivermectin, a drug commonly used to treat parasitic infections, for reducing seizures in people with epilepsy linked to onchocerciasis, also known as river blindness. Research shows that ivermectin not only targets the parasitic cause of the disease but may also help reduce brain inflammation, which plays a key role in epilepsy. While early results are promising, more research is needed to confirm whether ivermectin can be a reliable treatment for epilepsy in people affected by this condition.